2013
DOI: 10.4049/jimmunol.1203273
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D Promotes Negative Feedback Regulation of TLR Signaling via Targeting MicroRNA-155–SOCS1 in Macrophages

Abstract: The negative feedback mechanism is essential to maintain effective immunity and tissue homeostasis. 1,25-dihydroxyvitamin D (1,25(OH)2D3) modulates innate immune response, but the mechanism remains poorly understood. Here we report that vitamin D receptor (VDR) signaling attenuates Toll-like receptor-mediated inflammation by enhancing the negative feedback inhibition. VDR inactivation leads to hyper inflammatory response in mice and macrophage cultures when challenged with lipopolysaccharide (LPS), due to miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
152
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(168 citation statements)
references
References 57 publications
15
152
0
1
Order By: Relevance
“…Transfection of IKKβ dramatically induced the luciferase activity of the WT reporter, but not of the mutant reporter, and this induction was also markedly abrogated by 1,25(OH) 2 D 3 ( Figure 9F). Moreover, IKK kinase assays demonstrated that 1,25(OH) 2 D 3 blocked TNF-α-induced IKK activity to phosphorylate IκBα in HCT116 cells ( Figure 9G), confirming our previous finding that 1,25(OH) 2 D 3 /VDR signaling is able to block NF-κB activation (52)(53)(54). To verify that 1,25(OH) 2 D 3 downregulates PUMA by targeting NF-κB activation, we transfected HCT116 cells with an HA-IKKβ-expressing plasmid.…”
Section: Reconstitution Of Vdr-null Epithelial Cells With Hvdr Rescuesupporting
confidence: 89%
See 1 more Smart Citation
“…Transfection of IKKβ dramatically induced the luciferase activity of the WT reporter, but not of the mutant reporter, and this induction was also markedly abrogated by 1,25(OH) 2 D 3 ( Figure 9F). Moreover, IKK kinase assays demonstrated that 1,25(OH) 2 D 3 blocked TNF-α-induced IKK activity to phosphorylate IκBα in HCT116 cells ( Figure 9G), confirming our previous finding that 1,25(OH) 2 D 3 /VDR signaling is able to block NF-κB activation (52)(53)(54). To verify that 1,25(OH) 2 D 3 downregulates PUMA by targeting NF-κB activation, we transfected HCT116 cells with an HA-IKKβ-expressing plasmid.…”
Section: Reconstitution Of Vdr-null Epithelial Cells With Hvdr Rescuesupporting
confidence: 89%
“…Briefly, lysates prepared from HCT116 cells or colonic mucosa were immunoprecipitated with anti-IKKγ antibodies (Santa Cruz Biotechnology Inc.). The precipitant was incubated with recombinant GST-IκBα (amino acids 1-54; Clontech) in the presence of γ-32 P-ATP, and 32 P-labeled GST-IκBα (amino acids 1-54) was detected by autoradiography as described previously (58).…”
Section: Methodsmentioning
confidence: 99%
“…TLR4-mediated activation of NF-kB induces a negative feedback by upregulating miR-21 and miR-146, which ultimately dampen TLR-induced signaling and cytokine expression (22). In contrast, miR-155 shows anti-and proinflammatory effects by regulating TAB2 and SOCS1, respectively (23,24). Although these miRNAs are associated with fine-tuned inflammatory responses, miRNA-mediated regulation of neuroinflammation during viral infection has not been investigated in detail.…”
mentioning
confidence: 99%
“…In macrophages, the active form of vitamin D (1,25(OH)2D3) cause a reduction of gene expression and protein release of proinflammatory mediators, such as tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and monocyte chemo attractant protein-1 (MCP-1), result in reduction of monocytes/macrophages recruitment and overall inflammation within tissue [11][12][13].…”
Section: Introductionmentioning
confidence: 99%